Sedimentary host phases of mercury (Hg) and implications for use of Hg as a volcanic proxy - Shen, Jun; Feng, Qinglai; Algeo, Thomas J.; Liu, Jinling; Zhou, Chenyang; Wei, Wei; Liu, Jiangsi; Them, Theodore R.; Gill, Benjamin C.; Chen, Jiubin (Earth and planetary science letters, 2020)
•Sediment Hg can be hosted by the organic, sulfide or clay fractions.•Hg uptake by sulfide fraction favored under strongly euxinic conditions.•TS > 1.0% and TS/TOC > 0.35 linked to dominant sulfide host phase.•Dominant host phase must be determined for correct normalization of Hg volcanic proxy. Mercury (Hg) concentration enrichments have become a widely used proxy for volcanic inputs to sediments, especially for investigation of ancient large igneous province (LIP) eruptions. Its application for this purpose requires normalization to an element representing the dominant host phase of Hg–generally total organic carbon (TOC) for the organic fraction, but occasionally total sulfur (TS) or aluminum (Al) for the sulfide or clay fractions, respectively. Hg studies generally assume an organic matter host, but recent work has demonstrated that sulfide or clay fraction host phases are not uncommon, making it essential to determine formation-specific Hg host phases. Here, we investigate Hg concentrations and their relationships to TOC, TS, and Al in four modern marine settings (Black Sea, Japan Sea, Saanich Inlet, and Peru Margin) and six ancient marine formations (from Lower Cambrian to Lower Jurassic). Multiple regression analysis (MRA) shows that the organic fraction is the dominant host of Hg in all of the modern marine sediments examined here, as well as in many ancient marine units, although in some of the latter Hg resides primarily in the sulfide fraction (i.e., lower Cambrian and Upper Ordovician units) or partly in the clay mineral fraction (Middle Permian) of the sediment. A sulfide host phase is more likely in strongly euxinic depositional facies, as reflected in high TS concentrations (>1.0%) and TS/TOC ratios (>∼0.35). This study thus demonstrates the importance of determining Hg host phases in sediments prior to normalization and use of Hg as a volcanic proxy.